Ownership and governance of Finnish infrastructure networks - Leviakangas, Pekka; Talvitie, A.; Haapasalo, H.; Herrala, M.; Pakkala, P.; Nokkala, M.; Rönty, J.; Finnilä, K. (2011)
This research report investigates and analyzes the pros and cons of different ownership and governance models of infrastructure networks. The report covers most infrastructure networks: transportation networks (roads, streets, railways, airports, harbors) and utility networks (water and sewage, energy and electricity). There is no unifying solution that would fit all sectors in terms of the most efficient ownership model. However, in many sectors reforms are needed towards more elaborated client-supplier frameworks to ensure greater efficiency and cost transparency. Surprisingly, traditional organizational structures do not seem to impact on financial returns of those networks that provide user-financed services. In Finland technical infrastructure networks are typically owned, administered and managed by the public sector as they are considered public goods and critical assets for the wellbeing of citizens. In many ways the sectors have remained passive and with little interaction towards more innovative service provision solutions or organizational models. In terms of developing the networks’ services and their profitability, the greatest business opportunity would result from allowing open entry to market and competition in contracting. This would mean abandonment of negotiated contracts and proactive evolution of functional markets. The scope of business opportunities will increase in all aspect of service delivery; from management to engineering and economic studies, asset management systems, construction and maintenance works, and the labor to do all that.